The Philosophy of Education as a Framework for Literacy Culture Practices in Elementary Schools - Dinni, Dinni; Purwoko, Budi; Gunansyah, Ganes (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The philosophy of education is a crucial concept in the development of learning, particularly as the foundation for creating and advancing a program. It serves as an important bridge to clarify the direction of education in order to achieve specific goals. One of the most essential aspects is the development of literacy culture practices, which are based on several schools of thought within the philosophy of education. The development of literacy culture practices encompasses key streams, including philosophical, theoretical, and practical foundations. These practices aim to respond to the evolving state of literacy in Indonesia. This study employs a qualitative descriptive method by collecting data through interviews, literature reviews, and observations. The primary sources in this research include the thoughts of educators, schools, and communities, which are then aligned with the understanding of literacy culture. The results of this study reveal various streams of educational philosophy in observing the development of literacy culture in terms of its progress, implementation, and evaluation. Literacy culture is considered a vital component when viewed from the approach and schools of philosophical thought present in Indonesian education. This highlights that in every era and stage of development, literacy has served as a foundation for learning in formal schools across Indonesia.